Stigma Management among Children of Incarcerated Parents. Issue 11 (1st November 2016) - Luther, Kate
ABSTRACT: The stigma of incarceration can extend beyond the offender to his or her family, yet we know very little about how children of incarcerated parents manage their spoiled identity. Using interviews with 32 college students whose parents were incarcerated during their childhood, this study explored their stigma management techniques. Through grounded theory analysis, it became apparent that participants separated themselves from their incarcerated parent, viewed their incarcerated parent as a role model, and framed parental incarceration positively. These techniques allowed them to sustain a prosocial identity in light of their experience of parental incarceration.